THE EFFECT OF THE SCALES MEDIA USAGE TOWARD MASTERY OF THE WEIGHT MEASURING CONCEPT FOR STUDENT WITH INTELLECTUAL DISABILITY - Etika Nur Cahyani; Abdul Huda (Department of Special Education, 2016)
A student with intellectual disability who has low level of intelligence and adaptive skills, a weak and abstract thinking needs a special approach of learning. The concept of weight measuring on student with intellectual disability is an abstract concept. Mastering concept of weight happens on student with intellectual disability is that if there is an object which seems to be larger or more is definitely heavier. This concept implies on the learning approaches used by educators in instilling the concept of weight measurement correctly. Therefore, before students start to study about the concept of actual weight need to be bridged with the real concept of scales and weighing process to ascertain the nature of the weight of an object. The goal of this research was to describe the effect of the scales mediausage toward mastery of the weight measuring concept on student with intellectual disability in the class VII. The research design used in this study was Single Subject Research (SSR) with models A-B-A and using the unit of measuring scores. The results showed that there was the effect of the media on the mastery of weight scales concept. It was stated in the calculation of the overlap percentage between phases of baseline-1 to 0% of the intervention phase. This calculation stated that interventions have an impact on increasing the target behavior because the overlap percentages were below 90%. Peserta didik tunagrahita adalah anak yang memiliki keterbatasan taraf kecerdasan dan keterampilan adaptif. Karakteristik tunagrahita yang lemah dalam berpikir abstrak perlu suatu pendekatan pembelajaran. Konsep pengukuran berat pada siswa tunagrahita merupakan suatu konsep abstrak. Penguasaan konsep berat yang terjadi pada siswa tunagrahita bahwa benda yang kelihatan lebih besar atau lebih banyak pasti lebih berat. Konsep yang terjadi demikian berimplikasi pada pendekatan pembelajaran yang digunakan pendidik dalam menanamkan konsep pengukuran berat secara benar. Untuk itu, sebelum siswa melangkah mempelajari konsep berat yang sebenarnya perlu dijembatani dengan konsep nyata dari timbangan dan proses menimbang untuk memastikan sifat berat suatu benda.Tujuan penelitian ini adalah mendeskripsikan pengaruh penggunaan media timbangan terhadap penguasaan konsep pengukuran berat pada siswa tunagrahita kelas VII, Desain penelitian yang digunakan dalam penelitian ini adalah Single Subject Research (SSR) dengan model A-B-A dan menggunakan satuan ukur skor. Hasil penelitian menunjukkan adanya pengaruh penggunaan media timbangan terhadap penguasaan konsep berat. Hal ini dinyatakan dalam perhitungan persentase overlap antara fase baseline-1 ke fase intervensi sebesar 0%. Perhitungan tersebut menyatakan intervensi memiliki pengaruh terhadap peningkatan target behavior, karena persentase overlap berada di bawah 90%.